Understanding the Cultural Trauma behind Identity Creating a Third Space in the Middle of Polarity - Vivekananda, Ken Miryam; Christommy, Tommy (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
To anticipate the eternal polarization in the 2024 election, this study uses a critical perspective to trace the upstream of the problem of identity politics in Indonesia. By using digital ethnography methods, this study explores various narratives of cultural trauma that often circulate in the midst of election momentum as the root of the problem of identity politics. In this study, the psycho-social paradigm is used to read various narratives in Twitter conversations as a response to cultural trauma against social bodies that resist. By using a conceptual framework related to the process of forming a third space through digital media, this study offers a form of cultural trauma coping in a divided society.